2015
DOI: 10.1039/c5cp00060b
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of oxygen vacancies and hydroxyl group surface functionalized SnO2 nanoparticles

Abstract: We report, for the first time, the luminescence property of the hydroxyl group surface functionalized quantum dots (QDs) and nanoparticles (NPs) of SnO2 using low energy excitations of 2.54 eV (488 nm) and 2.42 eV (514.5 nm). This luminescence is in addition to generally observed luminescence from 'O' defects. The as-prepared SnO2 QDs are annealed at different temperatures under ambient conditions to create NPs with varying sizes. Subsequently, the average size of the NPs is calculated from the acoustic vibrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 44 publications
5
73
1
Order By: Relevance
“…Symmetry allowed A 1g at 632 cm −1 and defect, D mode at 570 cm −1 were observed in the Raman spectrum without TERS tip. The D mode at 570 cm −1 appears only in small size (diameter around 9 nm and below) SnO 2 nanostructures . Optically inactive A 2g mode was reported to appear at a value of 575 cm −1 following Matossi force constant model that considered modified bond length, space symmetry reduction and lattice distortion because of ‘O’ vacancies and local lattice disorders in SnO 2 NPs .…”
Section: Resultscontrasting
confidence: 59%
See 3 more Smart Citations
“…Symmetry allowed A 1g at 632 cm −1 and defect, D mode at 570 cm −1 were observed in the Raman spectrum without TERS tip. The D mode at 570 cm −1 appears only in small size (diameter around 9 nm and below) SnO 2 nanostructures . Optically inactive A 2g mode was reported to appear at a value of 575 cm −1 following Matossi force constant model that considered modified bond length, space symmetry reduction and lattice distortion because of ‘O’ vacancies and local lattice disorders in SnO 2 NPs .…”
Section: Resultscontrasting
confidence: 59%
“…In our earlier report we have demonstrated the photoluminescence related to -OH groups (which forms a defect energy state) in different size SnO 2 NPs including the 25-nm NPs using an excitation of 514.5 nm. [12] Xie et al [20] reported that the optical absorption of the laser because of defects in the metal oxides will cause the reduction in the Raman signal intensity. In the present case the defect energy state formed because of -OH groups might be absorbing some percentage of the laser (514.5 nm).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fu et al [36] reported that the ZnO QDs remained stable in water due to surface hydroxyl (OH) groups. It is noteworthy that the presence of high density of OH¯ on the surface of the SnO 2 QDs were disseminated by using FTIR and Raman spectroscopic studies [23]. The 25 nm NPs obtained after annealing at high temperature did not show such widely covered presence of OH¯ groups on the surfaces [23].…”
Section: Resultsmentioning
confidence: 98%